PENENTUAN Sr-90 DALAM SAMPEL BERAS DAN BEBERAPA SAYURAN DI SUMATERA BARAT - SARI, MAYA; Sarbaini, Sarbaini (Sainstek : Jurnal Sains dan Teknologi, 2013)
Rice and vegetables are the most of agriculture in West Sumatera. These are of environment media that needs reaserched to know how far the radioactivity level. This was done at environment laboratory of PTKMR-BATAN. Step of reaserch has been done as follow determining the location and take the samples, cultivating the samples in laboratory, measuring the samples with LBC and samples analysis. From the result of measurement it shown that the lowest concentrate could be measured by LBC device that was 0,093 mBq/Kg. Sr-90 concentrate into the result of reaserch shown the data with variation from undetected data (0,4749 ± 1,1422)mBq/Kg. Activity concentration Sr-90 which was found in the plants of agriculture result in West Sumatera land are the low than Java island area and lower than found in Japan.Key words: environment media, radioactivity level, LBC.